Pemenuhan kebutuhan pengetahuan dasar penyakit stroke pada masyarakat awam - Gumelar Zati Rahayu; hera maulidiyah; Hani Monika; Halidah Fauziah; Bangbang Erik Irawan (Yayasan Inspirasi El Burhani, 2021)
Introduction:Cerebrovascular injury or often referred to as a stroke is a sudden occurrence of neurological deficits due to the failure of the blood supply to a part of the brain. Insufficiency or interruption of the blood supply caused by thrombosis, usually secondary to arteriosclerosis, to embolism originating elsewhere in the body, or to bleeding from ruptured arteries. Objective: The activities carried out are to provide fulfillment of basic knowledge needs about this stroke. Stroke, also known as screbrovascular injury (CVA) is the cessation of blood supply to the brain and causes the function of part of the brain to disappear. Method: The method used in this counseling is based on strategy, implementation and action, ending with an evaluation carried out at the end of the extension with the number of questionnaires given to the community for the needs of the required research results. Results: The fulfillment of the need for basic knowledge about stroke to the community and the community can implement the results of counseling in accordance with the directions that have been given. Conclusion: The implementation is divided into several dimensions, namely timeliness and duration, participation, knowledge and problem solving. Work and evaluation carried out by 5 observators.